On Some Aspects of Word , Image and Human Values as Reflected by Russian Orthodox Icons and Western Religious Paintings - Andrzej Dudek (Ksiegarnia Akademicka Publishing, 2021)
The main focus of interest in the paper is the attitude of Western and Eastern stems of Christianity towards religious painting with reference to the problem of equality of word and image as far as the Church teaching is concerned. The roots and basic notions of Christian anthropology as well as positions revealed by both Churches during the discussions in 7-8th centuries are regarded as foundations for noticeable differences in interpretations of meanings, means, artistic principles, reality representations, ways of passing on the truth on man in Orthodox icons and Western religious paintings either. Taking in to account the relationship between object and its representation the paper develops the idea of metonymical principle being crucial for Western religious paintings and symbolic connection between signans belonging to the earthly reality and signatum pointing out to transcendent realm in Orthodox icon painting.